Family Formation in Ireland Trends, Data Needs and Implications: Report to Family Affairs Unit, Department of Social, Community and Family Affairs - Fahey, Tony; Russell, Helen (ESRI, 2001)
This study provides an overview of existing knowledge regarding the family in Ireland today. It focuses in particular on three major issues: the long-term decline in fertility, the growth and pattern of lone parenthood and changes in household and family size. It emphasises how poor the existing Irish data relating to the family are, and suggests how they could be improved.